Primary Biliary Cirrhosis - Irvan Nugraha; Guntur Darmawan; Emmy Hermiyanti Pranggono; Yudi Wahyudi; Nenny Agustanti; Dolvy Girawan; Begawan Bestari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Primary biliary cirrhosis (PBC) is an inflammatory disease or chronic liver inflammation, with slow progressive characteristic and is an unknown cholestatic liver disease and commonly happen in middle-aged women. The incidence of PBC is 0.03 – 5.8 per 100,000 people per year, prevalence of 1.91-40.2 per 100,000 people and continues to increase. Based on the American Association for Study of Liver Disease criteria, the diagnosis of PBC is made in the presence of two out of three criteria, which are increase of alkaline phosphatase, positive antimitochondrial antibodies (AMA), and histopathology examination.We reported a case which is very rarely found; a 47-year-old women with the chief complaints of decrease consciousness and jaundice. In physical examination, there were anaemic conjunctiva, icteric sclera, hepatosplenomegaly, palmar erythema, and liver nails. In the patient, there was no evidence of obstruction in imaging with two-fold increase of alkaline phosphatase and positive AMA test. Patient was hospitalised to slow down the progression of the disease and to overcome the signs (e.g. pruritus, osteoporosis and sicca syndrome).